2020
DOI: 10.3389/fpls.2020.01115
|View full text |Cite
|
Sign up to set email alerts
|

Dormant but Active: Chilling Accumulation Modulates the Epigenome and Transcriptome of Prunus avium During Bud Dormancy

Abstract: Temperate deciduous fruit tree species like sweet cherry ( Prunus avium ) require long periods of low temperatures to trigger dormancy release and flowering. In addition to sequence-based genetic diversity, epigenetic variation may contribute to different chilling requirements among varieties. For the low chill variety ‘Royal Dawn’ and high chill variety ‘Kordia’, we studied the methylome of floral buds during chilling accumulation using MethylC-seq to identify differentially methylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…DNA methylation and small interfering RNA (siRNA) might be involved in the regulation of MADS-box genes in sweet cherry during the dormancy transition 100 . More recently, Rothkegel et al demonstrated that DNA methylation might act as an early sensor of low temperature, leading to genotype-specific reprogramming and thus changing gene expression 105 .…”
Section: Endodormancy Maintenance and Release In Deciduous Fruit Treesmentioning
confidence: 99%
“…DNA methylation and small interfering RNA (siRNA) might be involved in the regulation of MADS-box genes in sweet cherry during the dormancy transition 100 . More recently, Rothkegel et al demonstrated that DNA methylation might act as an early sensor of low temperature, leading to genotype-specific reprogramming and thus changing gene expression 105 .…”
Section: Endodormancy Maintenance and Release In Deciduous Fruit Treesmentioning
confidence: 99%
“…From methylome results, both in normal and mealy fruits, cytosine methylation was higher in the CpG context, followed by CHG and CHH, coinciding with previous methylome studies of Arabidopsis thaliana, apple (Malus domestica borkh. ), Populus euphratica and sweet cherry (Prunus avium L.), showing that different pathways regulate DNA methylation (Lister et al, 2008;Daccord et al, 2017;Su et al, 2018;Rothkegel et al, 2020). Three biological replicates were considered as three independent fruits.…”
Section: Discussion the Methylome Of P Persica Fruits Reveals Epigenomic Differences Between Normal And Mealy Fruits Associated With Genementioning
confidence: 99%
“…A more recent study in tomato also showed that cytosine demethylation by a DNA glycosylase SIDML2/ROS1 is necessary for the activation of ripening-induced genes and inhibition of ripening-repressed genes, revealing a critical role for DNA methylation during fruit ripening ( Lang et al, 2017 ). In addition, changes in DNA methylation can be further used for the identification of novel markers, which will consider the genetic background, together with changing environmental conditions, as recently studied in Prunus ( Prudencio et al, 2018 ; Rothkegel et al, 2020 ). In this sense, molecular approaches associated with agronomical traits should be implemented together with classical genetics in order to support breeding programs ( García-Gómez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model does not explain; however, the role of transcriptional regulators and environmental factors that affect induction of endodormancy, such as, the MADS-box transcription factors or temperature dependent growth cessation [ 15 , 16 ]. Recent work in cherry trees, suggests that epigenetic regulation could play a vital role in dormancy transitions resulting in large-scale transcriptomic modification and an increase in expression of chromatin remodeling proteins [ 13 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few miRNAs show a more direct role in dormancy-associated processes. Crosstalk between miR6390 and C-repeat binding factor (CBF ) , dormancy-associated MADS-box (DAM) and flowering locus T (FT2) genes play important roles in regulating endodormancy in pear and cherry flower buds and other trees [ 10 , 17 , 20 , 22 ]. Similarly, both miRNA156 and miRNA172 were found to regulate seed dormancy and flowering time in lettuce ( Lactuca sativa ) and Arabidopsis thaliana in a delay of germination 1 (DOG1) dependent manner [ 21 ].…”
Section: Introductionmentioning
confidence: 99%